2014
DOI: 10.1016/j.mib.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pathogens are platforms for discovering novel and conserved septin properties

Abstract: Septins are filament-forming GTP-binding proteins that act as scaffolds in diverse cell functions including division, polarity and membrane remodeling. In a variety of fungal pathogens, it has been observed that septins are required for virulence because cells are unable to survive or are misshapen when septins are mutated. Cell morphology is interconnected with pathogenesis and thus septin mutants displaying aberrant cell morphologies are commonly deficient in host tissue invasion. The degree to which septins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…They colocalize with actin and microtubules and might regulate their stability and activity (82). Four septins form palindromic hetero-octamers, which assemble into higher-order structures (16).…”
Section: Cellular Functions Of Endosomal Mrna Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…They colocalize with actin and microtubules and might regulate their stability and activity (82). Four septins form palindromic hetero-octamers, which assemble into higher-order structures (16).…”
Section: Cellular Functions Of Endosomal Mrna Transportmentioning
confidence: 99%
“…Cytoplasmic microtubules provide tracks for long-distance movement mediated by molecular motors such as kinesins and dynein (see below; 27,32,84). Recent advances have shown that higherordered septin filaments function as another cytoskeletal element supporting efficient hyphal growth (Figure 1; see below; 6,16).…”
Section: Introductionmentioning
confidence: 99%
“…Though these roles are undoubtedly important for fungal growth and pathogenesis, they have been extensively reviewed elsewhere (Joo et al, 2005; Gladfelter, 2006, 2010; Lindsey and Momany, 2006; Lichius et al, 2011; Hernandez-Rodriguez and Momany, 2012; Mostowy and Cossart, 2012; Spiliotis and Gladfelter, 2012; Bridges and Gladfelter, 2014). In this mini-review, we focus instead on the role of septins in the morphogenetic switch from non-polar to polar growth, generally seen in filamentous fungi as the formation of polar outgrowths, and the importance of this switch for tissue invasion and fungal pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, septins are thought to play an important role in the migration of neural precursors and later in establishing proper morphology (18 -20). Moreover, in fungal pathogens, septins are generally required for virulence and are thought to be directly involved in host tissue entry (21). This includes a variety of human pathogens, such as Candida albicans, as well as devastating plant crop pathogens, including Magnaporthe oryzae, the cause of rice blast disease (22)(23)(24).…”
mentioning
confidence: 99%